Transformation of traditional agriculture into successful IFS Model - Singh, Ishwar; Singh, S K; Kumar, Mahendra; Kumari, Shilpa; Singh, Garbar (Indian Farming, 2021)
Zeal to acquire knowledge and its application under real farm situation has completely changed thescenario of farm of Shri Pukh Raj, a resident of village Balarwa in Jodhpur district. A massive changeat his farm can be seen as he has started growing new varieties and hybrids of crops and adopted IPMin vegetables with growing seedlings in net house. In a farmer-scientist interaction arranged at his farmunder FFP, he was apprised with protected cultivation, rain water harvesting and floriculture. Headopted all these ventures perfectly and at present he is earning 10-12 lakhs of additional income bygrowing cucumber under protected cultivation and Pusa Narangi marigold as new crops. The qualityof dried leaves of mint grown at his farm has been improved, as drying is done in high walk-in tunnelfacilitated at his farm under FFP. He is regular buyer of mineral bricks for his animals from CAZRIJodhpur. All these practices have increased his income by 35-40%. His is now a team leader and the GAPadopted by him are spreading rapidly in the nearby farms.